Botulinum neurotoxin: Not only in Dermatology - Expanding Therapeutic Horizons Across Medical Specialties - Kurzątkowska, Klaudia; Marszałek, Dominika; Ocimek, Aleksandra; Czudowska, Michalina; Zawadzka, Magdalena; Borychowska, Emilia; Gwóźdź, Karolina; Mierzejewska, Zofia Aneta; Drozdowska, Marta; Bystros, Aleksandra Natalia (Journal of Education, Health and Sport, 2026)
Background. Botulinum neurotoxin (BTX) is commonly associated with cosmetic applications; however, its therapeutic relevance extends far beyond aesthetic medicine. Through inhibition of presynaptic acetylcholine release, BTX induces reversible chemodenervation and modulates sensory, autonomic, and inflammatory signaling, providing a biological basis for its wide range of clinical applications across multiple medical specialties. Aim. The aim of this review was to summarize and critically appraise current evidence on established and emerging therapeutic applications of botulinum neurotoxin in dermatology, neurology, urology, gastroenterology, and selected novel indications. Material and methods. A narrative review of the literature was conducted using recent clinical studies, systematic reviews, meta-analyses, and relevant experimental research focusing on the mechanisms of action, clinical efficacy, and safety of botulinum neurotoxin across different medical disciplines. Results. Botulinum neurotoxin demonstrates well-established efficacy and an acceptable safety profile in dermatology, particularly in wound healing and hyperhidrosis, and in neurology, where it represents a cornerstone therapy for focal dystonias, spasticity, chronic migraine, and selected pain syndromes. In urology and gastroenterology, BTX provides effective, minimally invasive treatment options for refractory lower urinary tract dysfunctions and selected gastrointestinal and anorectal disorders. Emerging evidence further suggests potential roles for BTX in depression and immunomodulation. Conclusions. Botulinum neurotoxin has evolved into a versatile therapeutic agent with broad clinical applicability across multiple medical specialties. While its established indications are supported by robust evidence, emerging applications highlight promising new therapeutic directions that warrant further high-quality clinical and translational research.